The public and the private: the making of history in I Viceré - Pagliaro, Annamaria (Spunti e Ricerche, 2016)
In this study, rather than a reiteration of the novel's evident pessimism towards the historical period there is a consideration, in a Bakhtinian sense, of the dialogism in the novel in its plurality of voices, movement and interrelations, revealing a more complex signification than that given by its dominating point of view. There is a focus on the ignored, more subtle, critical voice which interprets the changes brought about by the Risorgimento and on the subjective, deformed perspective of the Uzeda. The complex dialogism in the novel offers a non-concluding and open-ended perspective: through history one is led to a more universal reflection on human nature and to a consideration of the process of interpreting history itself.